أصول التربية والذكاء الاصطناعي فرص وتحديات (Comprehensive Journal of Science, 2026)
This study aims to shed light on the difficulties that artificial intelligence faces when used in the field of education. Many educational systems suffer from numerous problems, such as weak educational policies and the lack of preparedness of most countries to provide distance education, especially due to the absence of digital curriculum updates. The study found that integrating artificial intelligence into education opens the door to many challenges, including ethical and value-related aspects, as well as social, educational, and cultural issues, in addition to technical and administrative challenges. It also highlights the importance of developing an educational vision for the future that balances benefiting from the capabilities of artificial intelligence with preserving human and educational principles.
Keywords: Foundations of Education; Artificial Intelligence; Opportunities; Challenges; Future Vision